Mitochondrial dysfunction in animal models of PTSD: Relationships between behavioral models, neural regions, and cellular maladaptation - Kaplan, Gary B.; Dadhi, Neysa A.; Whitaker, Carius S. (Frontiers in Physiology, 2023)
Post-traumatic stress disorder (PTSD) is a trauma-related condition that produces distressing fear memory intrusions, avoidance behaviors, hyperarousal, stress responses, insomnia and other symptoms. This review of rodent models of PTSD examines trauma effects on fear-related learning, cognition, and avoidance, emotional and arousal behaviors and on mitochondrial dysfunction in relevant neural pathways. The review focuses on research that includes four elements: consensus PTSD rodent models, behavioral phenotyping, mitochondrial dysfunction within key neural regions. This approach allows for the integration of behavioral, neural and cellular findings in PTSD models. The PTSD models reviewed include fear conditioning, predator/social stress, chronic restraint stress, single prolonged stress, social isolation, chronic unpredictable stress and early life stress. These models produce a variety of PTSD-related behaviors that include associative and non-associative fear- and stress-related responses, hyperarousal, avoidance behaviors, cognitive disturbances, social withdrawal, compulsive behaviors, anhedonia-, anxiety- and depression-related behaviors. Neural regions included fear- and stress-related regions of the prefrontal cortex, hippocampal, amygdala, nucleus accumbens and hypothalamus. PTSD models produced mitochondrial dysfunction that includes dysregulation of oxidative phosphorylation and other metabolic pathways including beta-oxidation of fatty acids and the tricarboxylic acid pathway. These models generative neural reactive oxygen species that damage DNA, proteins, and lipids. Trauma models further altered mitochondrial stucture and replication and affected neuroinflammatory responses, signal transduction and apoptosis. Antidepressant medications used for the treatment of PTSD reversed stress-induced changes in some PTSD-like behaviors and many elements of brain mitochondrial dysfunction. Future studies can develop PTSD models which are ecologically valid and result in a broader manifestation of PTSD-related behaviors as it is clinically defined. This review highlights mitochondrial mechanisms associated with PTSD-like behaviors that have been produced in an array of consensus PTSD models and identifies putative circuit-based targets for more effective treatment for this debilitating disorder.